2021
DOI: 10.3390/app11010442
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antibacterial Activity of Nepeta × faassenii Bergmans ex Stearn Essential Oil

Abstract: This study was designed to evaluate, for the first time, the antioxidant and antimicrobial activities of Nepeta × faassenii essential oil (NEO). Twenty-six compounds were identified by gas chromatography and mass spectrometry analysis, of which 4a alpha,7alpha,7a alpha-nepetalactone (34.12%), elemol (23.23%), spiro(5,6)dodecane (13.73%), and 3,4 alpha-dihydro-4a alpha, 7 alpha, 7a alpha-nepetalactone (7.93%) were the major compounds. The NEO exhibited broad-spectrum antibacterial effects, and possesses potent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
2
11
0
Order By: Relevance
“…In this regard, the EOs of different species of Nepeta has also been studied for their DPPH radical scavenging activity and their ability has been proven. The strong activity of the N. mahanesis EO agrees with the reported antioxidant activity of N. faassenii EO [ 48 ]. It is worth mentioning that the IC 50 value obtained in this study is lower than those reported for the EO of N. schiraziana (IC 50 = 52.24 µg/mL) [ 35 ] and N. flavida (IC 50 = 42.8 µg/mL) [ 49 ], indicating the stronger radical scavenging activity of N. mahanesis .…”
Section: Discussionsupporting
confidence: 87%
“…In this regard, the EOs of different species of Nepeta has also been studied for their DPPH radical scavenging activity and their ability has been proven. The strong activity of the N. mahanesis EO agrees with the reported antioxidant activity of N. faassenii EO [ 48 ]. It is worth mentioning that the IC 50 value obtained in this study is lower than those reported for the EO of N. schiraziana (IC 50 = 52.24 µg/mL) [ 35 ] and N. flavida (IC 50 = 42.8 µg/mL) [ 49 ], indicating the stronger radical scavenging activity of N. mahanesis .…”
Section: Discussionsupporting
confidence: 87%
“…The latter one is a characteristic constituent of this species. A previous study reported that this compound was a major one in the leaf EO of the same species [ 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…The method described by Danciu et al and Jianu et al [ 38 , 41 ], with minor modifications, was employed to determine the MBC and MFC. Up to 1 µL from each test tube with no visible growth was inoculated on Columbia agar supplemented with 5% sheep blood and incubated for 24 h at 37 °C for bacterial strains or on Sabouraud Dextrose agar supplemented with chloramphenicol and incubated at 28 °C for Candida strains.…”
Section: Methodsmentioning
confidence: 99%